Infection control behaviours, intra‐household transmission and quarantine duration: a retrospective cohort analysis of COVID‐19 cases. (18th August 2022) - McCarthy, Kate L.; James, Douglas P.; Kumar, Nikhil; Hartel, Gunter; Langley, Matthew; McAuley, Duncan; Bunting, Julie; Rushbrook, Elizabeth; Bennett, Cameron
Abstract: Objectives : To study COVID‐19 (Delta Variant) cases and close contacts co‐located within households. Focusing on epidemiology of transmission of COVID‐19, quarantine duration and utilisation of infection control behaviours under a telehealth model of care in an elimination setting. Methods : A retrospective cohort analysis examined household spread of infection, duration of quarantine and change in PCR CT value during illness. A survey explored infection control behaviours used by household members during isolation and quarantine. Results : The cohort was 141 individuals in 35 households. Thirty‐seven were index cases, and 48 became positive during quarantine, most within 10 days. Whole‐household infection occurred in 12 households with multiple members. Behaviours focused on fomite transmission reduction rather than preventing aerosol transmission. The median duration of close contact household quarantine was 25 days. The majority of COVID‐19 cases were de‐isolated after 14 days with no evidence of further community transmission. Conclusion : Intrahousehold transmission was not universal and, if it occurred, usually occurred quickly. Behaviours utilised focused on fomites, suggesting a need for improved education regarding the potential utilisation of strategies to prevention the transmission of aerosols. Households experienced long durations of home‐based quarantine. Implications for public health : The impact of long quarantine durations must be considered, particularly where most community benefit from quarantine is achieved within 10 days from exposure in the setting of the Delta Variant. Education of households regarding aerosol risk reduction is a potential strategy in the household setting of individuals at risk of disease progression.